Aneurisrna of the ascending portion of the aorta. (Disclaimer of mediastinal tumor Article Why?) - Odriozola, Ernsto (1918)
In one of our first lessons, we deal with the patient who is lying in bed No. 6 of our living history and whose comments appeared in No. 2 of "The Annals of the Faculty of Medicine". We did not make a categorical diagnosis, for the reasons that you already know and are found exposed in detail in the article alluded. Since that time they are three months elapsed, and it is necessary to return to this case because the situation has changed in terms that allow us and come to an accurate diagnosis